IMPROVING MARKETING PERFORMANCE HANAN CATERING DURING THE COVID-19 PANDEMI - Wandi Kurniadi; Annisha Suvero Suyar; Norvadewi Norvadewi (Jurnal Ekonomi, 2023)
In this study aims to determine the influence between entrepreneurial orientation and innovation variables on marketing performance. This research uses quantitative methods. The population in this study is the owner of UMKM Hanan Catering in the city of Bandung and the sample used is 36 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially between entrepreneurial orientation and innovation variables have a positive and significant impact on marketing performance. The results of the f test are known from the value of Fcount 44.229 > 3, 28 shows that the value of Fcount is greater than Ftable and from the results of the correlation in this study has a very strong and high value of 0.737. Meanwhile, from the results of the t test value, namely Tcount 3.555 > 1.692, it shows that Tcount is greater than Ttable so it can be concluded that entrepreneurial orientation and innovation variables have an influence on marketing performance.